Thyroid Hormone Therapy for Potential Heart Donors: A Comprehensive Review of Clinical Trials - Mushood Ahmed; Eeshal Zulfiqar; Sonia Hurjkaliani; Aimen Shafiq; Hafsa Arshad Azam Raja; Areeba Ahsan; Aemen Kamran; Laveeza Fatima; Amna Nadeem; Muhammad Abdullah Naveed; Faizan Ahmed; Hritvik Jain; et al. (Biomedicines)
Background: Due to neurohormonal disturbances that occur following brain death, thyroid hormone therapy has been proposed as a means to enhance cardiac function in brain-dead organ donors. However, it remains unclear whether thyroid hormone administration improves clinical outcomes in potential heart donors. Methods: A comprehensive review of clinical trials was conducted to evaluate the impact of thyroid hormone therapy on heart viability and transplantation outcomes. A total of nine randomized controlled trials (RCTs) involving 1189 potential heart donors were included. Results: Thyroid hormone supplementation effectively restored circulating thyroid hormone levels in brain-dead donors. However, findings regarding improvements in cardiac function and transplantation outcomes were inconsistent across studies. While some RCTs reported marginal improvements in hemodynamic parameters and heart transplant viability, these results were not consistently replicated. Furthermore, most studies did not demonstrate a significant enhancement in recipient survival or graft function associated with thyroid hormone therapy. Conclusion: Although thyroid hormone therapy restores thyroid hormone levels in brain-dead donors, current evidence does not consistently support its effectiveness in improving donor heart viability or recipient outcomes. Further research is necessary to clarify the role of thyroid hormone therapy in donor management and its impact on long-term transplant success.